2003
DOI: 10.1196/annals.1304.010
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Agmatine on Acute and Mononeuropathic Pain

Abstract: Agmatine is a polycationic amine synthesized from L-arginine by arginine decarboxylase in brain and several tissues. It binds to N-methyl-D-aspartate (NMDA) subtype of glutamatergic, alpha(2)-adrenergic and imidazoline (I) receptors. The present study was designed to investigate effect of agmatine on acute and mononeuropathic pain after chronic constriction injury (CCI). CCI was created by four loose ligations around the right sciatic nerve. The analgesic threshold in rats was evaluated by using thermal hypera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…It antagonizes a 2adrenoceptors, imidazoline receptors as well as Nmethyl-D-aspartate (NMDA) and glutamate receptors and inhibits nitric oxide synthase (NOS) [9]. Previous studies reported that agmatine has antinociceptive activity in several animal models of neuropathy or other behavioral models of pain [11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…It antagonizes a 2adrenoceptors, imidazoline receptors as well as Nmethyl-D-aspartate (NMDA) and glutamate receptors and inhibits nitric oxide synthase (NOS) [9]. Previous studies reported that agmatine has antinociceptive activity in several animal models of neuropathy or other behavioral models of pain [11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Our research group and others have demonstrated that exogenously administered agmatine has a variety of pharmacological effects related with central nervous system, such as nociception, neuroinjury/neuroprotection, cognition, epilepsy, opioid tolerance/ dependence, stress, anxiety, depression, and schizophrenia. Thus, agmatine can be a new candidate of novel therapeutic target by further revealing the underlying molecular mechanisms in related physiological and pathological conditions [20][21][22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…Our group and other research groups have repeatedly demonstrated that exogenous agmatine has a variety of pharmacological effects improving a wide spectrum of central nervous system conditions, such as algesia including neuropathic pain , mood disorders , epilepsy , morphine type addiction , neuroinjury and cognition . Perhaps one of the most well‐established effects are antistress, anxiolytic and antidepressant‐like effects produced by agmatine .…”
mentioning
confidence: 98%